Symptom Management: The Effects of Self-Affirmation on Chemotherapy-Related Symptoms. - Yildirim, Meltem; Gulsoy, Hatice; Batmaz, Makbule; Ozgat, Cansu; Yesilbursali, Gulser; Aydin, Reyhan; Ekiz, Sedanur (My University, 2017)
Positive effects of auditory stimulations are common in symptom management. However, the effect of self-affirmations on symptom management is not well known.

The purpose of this study is to investigate the effects of self-affirmations and nature sounds on chemotherapy-related symptoms.

This randomized, controlled experimental study was conducted with 140 patients receiving chemotherapy. The first experimental group listened to affirmations, the second listened to nature sounds, and the third listened to both.

In the affirmation group, pain, tiredness, drowsiness, lack of appetite, depression, anxiety, and lack of well-being scores were lower. In the affirmation and nature sounds group, drowsiness, depression, anxiety, and lack of well-being scores were reduced. In the nature sounds group, tiredness, drowsiness, and lack of well-being scores were reduced. In the control group, tiredness, drowsiness, nausea, and lack of well-being scores were higher.
Keywords: chemotherapy; nature sounds; self-affirmations; symptom management; nursing care